Methyl mercury triggers endothelial leukocyte adhesion and increases expression of cell adhesion molecules and chemokines. Issue 23 (December 2021) - Fowler, Joshua; Tsui, Martin Tsz-Ki; Chavez, Jessica; Khan, Safeera; Ahmed, Hassan; Smith, Lena; Jia, Zhenquan
Cardiovascular disease is the leading cause of morbidity, mortality, and health care costs in the USA, and around the world. Among the various risk factors of cardiovascular disease, environmental and dietary exposures to methyl mercury, a highly toxic metal traditionally labeled as a neurotoxin, have been epidemiologically linked to human cardiovascular disease development. However, its role in development and promotion of atherosclerosis, an initial step in more immediately life-threatening cardiovascular diseases, remains unclear. This study was conducted to examine the role that methyl mercury plays in the adhesion of monocytes to human microvascular endothelial cells (HMEC-1), and the underlying mechanisms. Methyl mercury treatment significantly induced the adhesion of monocyte to HMEC-1 endothelial cells, a critical step in atherosclerosis, while also upregulating the expression of proinflammatory cytokines interleukin-6, interleukin-8. Further, methyl mercury treatment also upregulated the chemotactic cytokine monocyte chemoattractant protein-1 and intercellular adhesion molecule-1. These molecules are imperative for the firm adhesion of leukocytes to endothelial cells. Additionally, our results further demonstrated that methyl mercury stimulated a significant increase in NF-κB activation. These findings suggest that NF-κB signaling pathway activation by methyl mercury is an important factor in the binding of monocytes to endothelial cells. Finally, by using flow cytometric analysis, methyl mercury treatment caused a significant increase in necrotic cell death only at higher concentrations without initiating apoptosis. This study provides new insights into the molecular actions of methyl mercury that can lead to endothelial dysfunction, inflammation, and subsequent atherosclerotic development.